Function and Inhibitory Mechanisms of Multidrug Efflux Pumps - Nishino, Kunihiko; Yamasaki, Seiji; Nakashima, Ryosuke; Zwama, Martijn; Hayashi-Nishino, Mitsuko (Frontiers in Microbiology, 2021)
Multidrug efflux pumps are inner membrane transporters that can export multiple antibiotics from the inside to the outside of bacterial cells, contributing to bacterial multidrug resistance (MDR). Postgenomic analysis has demonstrated that numerous multidrug efflux pumps exist in bacteria. Also, co-crystal structural analysis of multidrug efflux pumps revealed the drug recognition and export mechanisms, and the inhibitory mechanisms of the pumps. A single multidrug efflux pump can export multiple antibiotics; hence, developing efflux pump inhibitors is crucial in overcoming infectious diseases caused by multidrug-resistant bacteria. This review article describes the role of multidrug efflux pumps in MDR, and their physiological functions and inhibitory mechanisms.